Phytotoxic Substances in Bangladeshi Allelopathic Rice BR 17 - Hisashi Kato-Noguchi; Abdus Salam; Masahiro Morokuma (Plant Production Science, 2014)
Aqueous methanol extracts of Bangladeshi rice (Oryza sativa L.) cultivar BR 17 inhibited the growth of roots and coleoptile of Echinochloa crus-galli extract-concentration dependently. The extracts were then purified by several chromatographic runs, and a phytotoxic active substance was isolated and identified by spectral analysis as (–)-3-hydroxy-β-ionone. The concentration of (–)-3-hydroxy-β-ionone in BR 17 was higher than that of two other phytotoxic substances, 9-hydroxy-4-megastigmen-3-one and 3-oxo-α-ionol, found in BR 17. The novel isolated (–)-3-hydroxy-β-ionone inhibited the growth of E. crus-galli at concentrations higher than 10 μM. Those phytotoxic substances may contribute to the allelopathic effect of BR 17. Therefore, the rice cultivar BR 17 may be potentially useful for weed management as a weed suppressing agent when incorporated into the soil or included in a rice-based cropping system.